Gaps and opportunities in addressing the needs of older adults in the Philippines and Vietnam: a qualitative exploration of health and social workers' experiences in urban care settings - TJ Robinson T. Moncatar; Man Thi Hue Vo; Kathryn Lizbeth L. Siongco; Tran Dai Tri Han; Kaoruko Seino; Kaoruko Seino; Aliya Vanessa D. Gomez; Carmelita C. Canila; Richard S. Javier; Thang Van Vo; Thang Van Vo; Yuri Tashiro; et al. (Frontiers Media S.A., 2024)
BackgroundDespite numerous government initiatives, concerns and disparities among older adults have continually been growing. Empirical studies focused on older adults in the Philippines and Vietnam appear minimal and mostly regarding perceptions of aging. An effective geriatric care strongly relies on functional service providers requiring their perspectives to be explored toward inclusive service delivery.ObjectiveTo investigate the perceived gaps and opportunities in geriatric care service delivery among health and social care workers in selected urban areas in the Philippines and Vietnam.MethodsA qualitative case study approach drawn on social constructivism theory, examined working experiences, observed characteristics of older adults, geriatric services and needs, difficulties on service delivery, and recommended solutions. A total of 12 semi-structured interviews and 29 focus group discussions were conducted in the Philippines, with 174 health and social care workers, while in Vietnam, there were 23 semi-structured interviews and 29 focus group discussions with 124 participants. An inductive thematic analysis was employed.ResultsInterview participants highlighted the increasing unmet needs such as accessibility, availability, and acceptability of geriatric care services. The implementation of interventions on the older population faced multiple challenges, including issues related to older adult conundrums and dilemmas in geriatric care providers and facilities. The participants from the two countries felt that strengthening implementation of collaboration toward an integrated geriatric care structure and expansion of training and capability in handling older adults can be potential in addressing the gaps at both individual and institutional levels. Additionally, a committed leadership was viewed to be the important step to effectively operationalize the strategy.ConclusionHealth and social workers emphasized that the needs of older adults are exacerbated by various challenges within a fragmented geriatric care system. To address this issue, an establishment of an integrated service delivery mechanism with dedicated leadership is needed. The findings from this study may help develop appropriate solutions for addressing the health and social care needs of older adults in similar settings across Southeast Asia. Further examination of the impact of these challenges and solutions on service delivery and the wellbeing of older adults is essential.